2013
DOI: 10.1128/aac.02381-12
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Proveblue (Methylene Blue) in an Experimental Cerebral Malaria Murine Model

Abstract: e Although 100% of untreated mice infected with Plasmodium berghei died with specific signs of cerebral malaria and 100% of mice treated with 3 mg/kg dihydroartemisinin, the active metabolite of artesunate, which is used as the first-line treatment for severe malaria, also died but showed no specific signs of cerebral malaria, 78% of mice treated with 10 mg/kg Proveblue (methylene blue) and 78% of mice treated with a combination of 3 mg dihydroartemisinin and 10 mg/kg Proveblue survived and showed no specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…In the mice treated with 10 mg/kg Proveblue for 5 days, one mouse (10%) died at D14 (10.5% parasitemia) with specific signs of CM and another died at D20 (85.9% parasitemia) with no specific signs of CM. Similar results were obtained for 10 mg/kg Proveblue for 5 days, with 78% of mice surviving after treatment (3,4). In the mice treated with 3 mg/kg for 5 days, three mice (30%) died between D23 and D26 (parasitemia between 81.3 and 93.1%) with no specific signs of CM.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…In the mice treated with 10 mg/kg Proveblue for 5 days, one mouse (10%) died at D14 (10.5% parasitemia) with specific signs of CM and another died at D20 (85.9% parasitemia) with no specific signs of CM. Similar results were obtained for 10 mg/kg Proveblue for 5 days, with 78% of mice surviving after treatment (3,4). In the mice treated with 3 mg/kg for 5 days, three mice (30%) died between D23 and D26 (parasitemia between 81.3 and 93.1%) with no specific signs of CM.…”
supporting
confidence: 72%
“…Proveblue exhibited noticeable synergistic effects in combination with mefloquine and quinine and high synergistic effects in combination with dihydroartemisinin, the active metabolite of artemisinin derivatives (2). Treatment with 10 mg/kg of body weight of Proveblue for 5 days significantly reduced or prevented cerebral malaria (CM) in mice (3,4). However, this dose was too high to show synergistic effects in combination with dihydroartemisinin or atorvastatin in malaria cerebral prevention.…”
mentioning
confidence: 99%
“…Interestingly, maprotiline, a tetracyclic antidepressant similar to the tricyclic antidepressant methylene blue, demonstrated nanomolar inhibition of both gametocyte and asexual stages of P. falciparum , but showed greater efficacy against gametocytes. Methylene blue has reported efficacy against gametocytes in vitro and also showed in vivo efficacy against asexual parasites in multiple murine models of cerebral malaria, protecting 75% of mice at 10 mg/kg for five days post-infection [9], [23][26]. Our observations suggest further exploration of tetracyclic and tricyclic antidepressants for gametocytocidal activity.…”
Section: Discussionsupporting
confidence: 51%
“…It is conceivable that MB can be considered for application in treatment of both uncomplicated and complicated malaria as well as for its potential for use in LM-and PYR-resistant malaria regions. This therapeutic potential is further highlighted in MB's capacity to efficiently manage cerebral malaria, a complication of untreated malaria [21].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated that MB is effective, with 50% inhibitory concentration at 3.62-3.90 nM, on 23 P. falciparum strains resistant to several standard antimalarials, including chloroquine (CQ) [20]. Dormoi et al [21] went on to further demonstrate significant efficacy of MB in the treatment and survival of cerebral malaria in mice infected with non-resistant P. berghei (p = 0.0011).…”
Section: Introductionmentioning
confidence: 99%